Development of the Integral Complex of Optimal Control of Heavy Machine Tools Adaptive Technological System for Wind-power Engineering Parts. (2015) - Kovalov, Viktor; Vasilchenko, Yana; Dašić, Predrag
Abstract: The work is aimed at improving the adaptive control efficiency for machining process on heavy machine tools. The integral complex of optimal control, which includes a heavy machine tool, systems of tools and tool management, adaptive control system with sets of measurement and diagnostic tools, the mathematical models of functioning of the technological system in terms of adaptive control developed. Ways to increase the efficiency and ecological compatibility of production and operation of machine tools in the manufacture of large-sized products for power purposes is studied in the paper.